Resveratrol Prevention of Diabetic Nephropathy Is Associated with the Suppression of Renal Inflammation and Mesangial Cell Proliferation: Possible Roles of Akt/NF-κB Pathway. (9th February 2014) - Xu, Feng; Wang, Yuehui; Cui, Wenpeng; Yuan, Hang; Sun, Jing; Wu, Man; Guo, Qiaoyan; Kong, Lili; Wu, Hao; Miao, Lining
Abstract : The present study was to investigate the protection of resveratrol (RSV) in diabetes associated with kidney inflammation and cell proliferation. Rat mesangial cell and streptozotocin-induced type 1 diabetes mouse model were used. In vitro, RSV attenuated high glucose-induced plasminogen activator inhibitor (PAI-1) expression and mesangial cell proliferation, as well as Akt and nuclear factor-kappa B (NF- κ B) activation. The similar results were recaptured in the experiment with Akt inhibitors. In vivo, mice were divided into three groups: control group, diabetes mellitus (DM) group, and RSV-treated DM group. Compared with control group, the kidney weight to body weight ratio and albumin to creatinine ratio were increased in DM group, but not in RSV-treated DM group. Furthermore, the increased expression of PAI-1 and intercellular adhesion molecule-1 in diabetic renal cortex were also reduced by RSV administration. Besides, the kidney p-Akt/Akt ratio and NF- κ B were significantly increased in DM group; however, these changes were reversed in RSV-treated DM group. Additionally, immunohistochemistry results indicated that RSV treatment reduced the density of proliferating cell nuclear antigen-positive cells significantly in glomeruli of diabetic mice. These results suggest that RSV prevents diabetes-induced renal inflammation and mesangial cell proliferation possibly through Akt/NF- κ B pathway inhibition.